Psychosocial work characteristics and psychological strain in relation to low-back pain - Hoogendoorn, Wilhelmina E.; Bongers, Paulien M.; de Vet, Henrica CW; Houtman, Irene LD; Ariëns, Geertje AM; van Mechelen, Willem; Bouter, Lex M. (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This study investigated the relationship between psychosocial work characteristics and low-back pain and the potential intermediate role of psychological strain variables in this relationship. ' ' METHODS ': 'The research was part of a prospective cohort study of risk factors for musculoskeletal symptoms. The study population consisted of 861 workers from 34 companies in The Netherlands who had no low-back pain at baseline and for whom data on the occurrence of low-back pain were obtained with annual questionnaires during a 3-year follow-up period. Information on psychosocial work characteristics and psychological strain variables was collected using a questionnaire at baseline. Cases of low-back pain were defined as workers who reported, in at least one of the annual follow-up questionnaires, that they had had regular or prolonged low-back pain in the previous 12 months. ' ' RESULTS ': 'After adjustment for individual factors and quantified physical load at work, nonsignificant relative risks ranging from 1.3 to 1.6 were observed for high quantitative job demands, high conflicting demands, low supervisory support, and low co-worker support. Decision authority and skill discretion showed no relationship with low-back pain. In general, the estimated relative risks for the psychosocial work characteristics were scarcely influenced by additional adjustment for job satisfaction, emotional exhaustion, and sleeping difficulties. ' ' CONCLUSIONS ': 'It can be concluded that low social support, from either supervisors or co-workers, appears to be a risk factor for low-back pain. Some indications of a relationship between high quantitative job demands and high conflicting demands and low-back pain were also found. Little evidence was found for an intermediate role for the psychological strain variables under study.
Keywords: industrial psychology; job satisfaction; low-back pain; prospective cohort study; psychological strain; psychological stress; psychosocial work characteristics; risk factor; social support